A Study on Personal Hygiene of School Going and Non-School Going Children in Ahmedabad District, Gujarat - Chaudhari, Ashish; Mansuri, Sohil; Singh, Anoop; Talsania, Niti (National Journal of Community Medicine, 2015)
Introduction: The word “Hygiene” was came from the Greek word “hygies” ( Hygiea- Goddess of Health) means Healthy, sound. Per- sonal hygiene may be described as the principle of maintaining cleanliness and grooming of the external body. Failure to keep up a standard of hygiene can have many implications. Methodology: Present study was conducted among 1378 school going and 697 non-school going children of 10 to 18 years of age during the period December 2012-December 2014 Result: Majority 24.86% of non-school going urban children have poor personal hygiene followed by 20.79% in non-school going ur- ban children. Poor personal hygiene was seen just 9.77% of School going children of urban area and 13.43% in rural area. Statistic dif- ference for poor personal hygiene among school going and non- school going children of urban area was highly significant Conclusion: There were huge differences on overall occurrence of personal hygiene, it was found almost double among non-school children compare to school children. Non school children were the most vulnerable group.